A Short Review of All-Dielectric Topological Photonic Crystals - Wang, Hai-Xiao; Jiang, Jian-Hua (Frontiers in Physics, 2022)
Topological photonics, as an emerging field that transfer the novel topological phases of matter to various photonic systems, offers an unprecedented opportunity for the manipulation of the electromagnetic waves. Here, we present a brief review on the development of topological photonics, and focus on several prominent milestones of works based on all-dielectric photonic crystals (PhCs) by discussing the topological invariants as well as the intriguing topological properties. These topological systems including 1D Su-Schrieffer-Heeger model, quantum Hall insulators, quantum spin-Hall insulators, valley Hall insulators, higher-order topological insulators and topological semimetals.